2016
DOI: 10.1186/s40478-016-0349-9
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome 1q gain and tenascin-C expression are candidate markers to define different risk groups in pediatric posterior fossa ependymoma

Abstract: Intracranial classic (WHO grade II) and anaplastic (WHO grade III) ependymomas are among the most common tumors in pediatric patients and have due to frequent recurrences and late relapses a relatively poor outcome. The impact of histopathological grading on patient outcome is controversial and therefore, molecular prognostic and predictive markers are needed to improve patient outcome. To date, the most promising candidate marker is chromosome 1q gain, which has been associated in independent studies with adv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
2
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 55 publications
4
34
2
4
Order By: Relevance
“…Therefore, patients with PFB ependymoma, particularly children are excellent candidates for radiation sparing strategies, where carefully controlled studies are being contemplated of observation alone in the setting of gross total resection. Gain of 1q has been proposed as a marker of poor prognosis in PFA ependymoma, however its role in PFB is unclear [1, 4, 7, 8, 17, 25]. We have also recently shown that PFA ependymoma are highly heterogeneous entities with two major groups with multiple subtypes[13].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, patients with PFB ependymoma, particularly children are excellent candidates for radiation sparing strategies, where carefully controlled studies are being contemplated of observation alone in the setting of gross total resection. Gain of 1q has been proposed as a marker of poor prognosis in PFA ependymoma, however its role in PFB is unclear [1, 4, 7, 8, 17, 25]. We have also recently shown that PFA ependymoma are highly heterogeneous entities with two major groups with multiple subtypes[13].…”
Section: Introductionmentioning
confidence: 99%
“…Gains of 12p have recently also been detected in prepubertal testicular teratomas, which represent Type I GCT in children . Furthermore, gain of chromosome 1q, which is known to be associated with poor prognosis in a variety of malignancies of the childhood (eg, Wilms tumor or pediatric brain tumors), was examined for its prognostic relevance in pediatric GCT …”
Section: Introductionmentioning
confidence: 99%
“…17 Furthermore, gain of chromosome 1q, which is known to be associated with poor prognosis in a variety of malignancies of the childhood (eg, Wilms tumor or pediatric brain tumors), was examined for its prognostic relevance in pediatric GCT. [18][19][20][21][22]…”
Section: Introductionmentioning
confidence: 99%
“…The alterations showed the following statistical values: to 1q (Tau2 = 1.53, I 2 = 45%, P = 0.02, χ 2 = 9.13), to 9p (Tau2 = 1.27, χ 2 = 6.84, I 2 = 42%, P = 0.24) to 6q (Tau2 = 0.00, χ 2 = 2.06, I 2 = 0%, P = 0.58), to 13q (Tau2 = 0.00, χ 2 = 0.08, I 2 = 0%, P = 0.14), and to 22q indicated perfect homogeneity (Tau2 = 0.00, χ 2 = 0.08, I 2 = 0%, P = 0.14). Over a wide range, our model indicated heterogeneity with the following statistical values: Tau2 = 1.72, χ 2 = 37.8, P = 0.01, [39] FISH, IHC Chromosomal alteration, protein 52 Chen et al 2016 [40] I H C P r o t e i n 1 7 4 Gojo et al 2017 [41] qRT-PCR Methylation and expression 24 a Immunochemistry, b polymerase chain reaction, c comparative genomic hybridization, d real-time polymerase chain reaction, e methylation-specific PCR, f array CGH, h fluorescence hybridization in situ I 2 = 0%. Therefore, chromosomal alterations in 1q, 6q, 9p, 13q, and 22q are features of pediatric ependymal tumors.…”
Section: Chromosomal Alterationsmentioning
confidence: 83%